Ako'y isang mabuting Pilipino I am a good Filipino - Cabangon, Noel (Lampara books, 2012)
"You can use this story as a springboard in discussing with children about being a good citizen of the Philippines-and the various good deeds and values that have to be cultivated in order to become a truly good Filipino."